Analysis of possibilities to use phase change materials in heat exchangers-accumulators - Pakalka, Saulius; Valančius, Kęstutis; Čiuprinskas, Kęstutis; Pum, Dominik; Hinteregger, Markus (International Conference “Environmental Engineering”, 2017)
Phase Change Materials (PCMs) are utilized in different engineering fields, such as thermal storage of building structures, such as domestic hot water, heating and cooling systems, electronic products, drying technology, waste heat recovery, refrigeration and cold storage, and solar cookers. The biggest technological problems for the implementation of low and high temperatures PCM are the insufficient thermal conductivity of the available phase change materials, compatibility with the container material, cycling stability. In order to evaluate efficient and cost effective operation of thermal energy storage, different design concepts for PCM integration into heat exchanger/ accumulator should be investigated.
Keywords: Heat exchanger; Phase change material (PCM); Latent heat; Thermal energy storage (TES)